Assessment of early prediction of mandibular third molar impaction by panoramic indices: A radiological study (Orthodontic Journal of Nepal, 2020)
Introduction: Mandibular third molar is one of the most frequently impacted tooth. The assessment and early prediction of the mandibular third molar impaction is of considerable clinical significance as it helps in early intervention so as to opt for its prophylactic removal. This reduces the risk of developing various pathologies like cysts, tumors, root resorption of adjacent teeth, pericoronitis etc, and also reduces risk of complications associated with extraction of fully developed tooth. The objective of this study is to compare different linear and angular measurements between the impacted and erupted mandibular third molar groups on digital panoramic radiograph and to assess the predictive validity of these panoramic measurements in mandibular third molar impaction.Materials and Method: 90 mandibular third molars were assessed using the linear and angular measurements made on digital panoramic radiograph. Mesiodistal width of mandibular third molar (MDW), lower eruption space- ramus (LES-R), lower eruption space- Rickett’s Xi (LES-Xi), alpha angle (α-angle), gamma angle (γ-angle) and gonial angle (Go-angle) were the measurements made. Space/width ratio 1 (R1) and space/width ratio 2 (R2) were also calculated. These parameters were compared between the impacted and erupted groups using Independent sample t-test and predictive validity with sensitivity and specificity of these parameters was assessed using ROC curve analysis.Result: LES-R, LES-Xi, R1, R2 and α-angle showed significant statistical difference between the impacted and erupted groups. R1 followed by R2, LES-R showed good predictive validity and LES-Xi showed fair predictive validity in mandibular third impaction.Conclusion: Decrease in lower eruption space, space/width ratio and increase in the mandibular third molar angulation favor impaction of the mandibular third molar. Among different panoramic linear and angular measurements, R1, R2 and LES-R can prove to be a relatively good predictor for mandibular third molar impaction.